1994
DOI: 10.1006/viro.1994.1641
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen Treatment of Adenovirus Particles Eliminates Virus Replication and Transcription While Maintaining the Endosomolytic Activity of the Virus Capsid

Abstract: Adenovirus entry into its host cell transiently permeabilizes the cell allowing the coentry of reagents such as DNA. We compare here adenovirus inactivation with beta-propiolactone and several psoralen derivatives, seeking reagents that disrupt the viral genome without impairing the viral entry functions. No virus replication can be detected after 8-methoxypsoralen (8-MOP) modification. Viral transcription is not detectable by Northern analysis, and reverse transcriptase/PCR analysis demonstrates at least a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 0 publications
0
54
0
Order By: Relevance
“…35 To obtain the non-replicating particle control, AdwtRGD UV-psoralen, the AdwtRGD was inactivated by UV-psoralen as previously described. 41 ICOVIR15 is a conditionally replicating adenovirus in which expression of the adenovirus E1A-D24 gene is regulated by a modified endogenous E1A promoter, which contains eight E2F-1-binding sites and one Sp1-binding site. To generate ICOVIR16, a shuttle plasmid, pNKFiberGALV, was constructed as follows.…”
Section: Methodsmentioning
confidence: 99%
“…35 To obtain the non-replicating particle control, AdwtRGD UV-psoralen, the AdwtRGD was inactivated by UV-psoralen as previously described. 41 ICOVIR15 is a conditionally replicating adenovirus in which expression of the adenovirus E1A-D24 gene is regulated by a modified endogenous E1A promoter, which contains eight E2F-1-binding sites and one Sp1-binding site. To generate ICOVIR16, a shuttle plasmid, pNKFiberGALV, was constructed as follows.…”
Section: Methodsmentioning
confidence: 99%
“…We confirmed the potency of magnetofection with calcium phosphate coprecipitation, naked DNA and polylysine-DNA (not shown). Compared with a naked DNA magnetofectin (which hardly yielded any transfection; data not shown), complexation with cationic lipids or PEI (Figure 2a and b), as well as the incorporation of the endosomolytic peptide INF7 11 (not shown) or a chemically inactivated adenovirus 9 (Figure 2a and c) enhanced transfection several thousand-fold. Therefore, the mechanisms of cellular uptake and vector processing are probably similar to those of the parent vectors, namely endocytotic.…”
Section: Nonviral Magnetofectionmentioning
confidence: 97%
“…We formulated state-of-the-art nonviral and viral gene vectors (PEI-DNA, 8 AVET, 9 Lipofectamine, GenePorter and DOTAP-Cholesterol, 10 recombinant adenovirus and a retrovirus) as magnetofectins and compared reporter gene expression levels achieved with short-term incubation to the parent standard vector formulations. The data show that the formulation with paramagnetic nanoparticles alone enhanced transfection, while the application of a magnetic field raised reporter gene expression levels up to three orders of magnitude over those achieved with standard vectors under the same conditions ( Figure 2a, nonviral vectors; Figure 3, adenoviral vector; Figure 4, retroviral vector).…”
Section: Gene Therapymentioning
confidence: 99%
“…For studies using a neutralizing antibody (Virostat, 1401, Portland, ME, USA), a 1:100 dilution of antibody was incubated with 2 × 10 10 particles of virus for 30 min at room temperature before formation of coprecipitates. For some experiments, virus was inactivated by psoralen/UV treatment as described by Cotten et al; 29 the inactivated virus showed a greater than 10 6 decrease in titer. As a reporter plasmid, we used p␤Gal-NLS which expresses ␤-galactosidase; this plasmid was a gift of Dr Sam Wadsworth (Genzyme, Framingham, MA, USA).…”
Section: Vectors and Vector-related Reagentsmentioning
confidence: 99%